The green climate fund and its shortcomings in local delivery of adaptation finance. (26th November 2022) - Omukuti, Jessica; Barrett, Sam; White, Piran C. L.; Marchant, Robert; Averchenkova, Alina
ABSTRACT: The Paris Agreement recognizes the important role that local level actors play in ensuring climate change adaptation that contributes to meeting the global temperature goal. As a financial mechanism of the United Nations Framework Convention on Climate Change (UNFCCC) and the largest dedicated climate fund, the Green Climate Fund (GCF) is critical to achieving this goal. How GCF allocates its resources is therefore a critical area of research. This article assesses GCF's commitment to the local delivery of adaptation finance and identifies the key barriers to GCF's achievement of this commitment. The analysis finds that although GCF's policies and communications fully commit to funding local level adaptation, three key barriers still prevent it from delivering finance to the local level. First, GCF lacks a unified framework for identifying and defining the local level, local actors, and local adaptation processes. Second, GCF exhibits limited transparency and accountability in relation to how approved funding for adaptation is spent, particularly for projects that claim to generate local level adaptation outcomes. Third, some Accredited Entities have limited experience and capacity for designing and implementing projects that deliver finance to the local level. This is because the local delivery of finance is not prioritized by GCF during the accreditation of entities or provision of readiness support to Accredited Entities. Our findings indicate limited evidence of GCF's full operationalization of its commitment to supporting local adaptation. We recommend that GCF develop and apply a unified framework for defining what constitutes 'local'. Key policy insights: GCF is committed to supporting local adaptation finance in developing countries but has failed to adequately operationalize this commitment. To increase local delivery of climate finance, GCF should develop a unified framework for local delivery of adapation finance that emphasises local actors' leadership in design, implementation, and management of adaptation projects. GCF should also increase transparency and accountability of funded projects to enable independent assessments of local delivery of adaptation finance by making project information, including financial reports publicly available. GCF should ensure that Accredited Entities have capacity to develop and deliver projects that deliver adaptation finance to the local level e.g. by requiring entities to provide evidence of support for local adaptation during accreditation.